Timed-insemination of beef heifers using Cosynch with one or two initial injections of GnRH - Grieger, David M.; Holladay, C.D.; Eborn, D.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Our purpose was to determine if giving an additional injection of GnRH to beef heifers synchronized with the Cosynch protocol would increase pregnancy rate to timed A.I. Eighty yearling beef heifers received an injection of GnRH, 7 days before receiving an injection of PGF (Cosynch). One half of the heifers were also given an injection of GnRH 14 days prior to the PGF injection (2×GnRH-Cosynch). All heifers were given a GnRH injection 2 days after PGF and inseminated at that time. Pregnancy rate for the 2×GnRH-Cosynch group (40%) was not different than that for the Cosynch group (50%) and was actually numerically lower. This trial suggested that an additional injection of GnRH 1 week prior to the Cosynch protocol was not beneficial in increasing the pregnancy rate of heifers to timed A.I.
Keywords: Beef; Heifers; AI; Estrous synchronization; GnRh; PGF2α